Improving The Writing Skills Of Griya Santri Mahabbah Students ThroughTraining In The Use Of Publish Or Perish And Mendeley - Aini, Aisyah Nurul; Mustamtiroh, Qotrotul; Putri, Nanda Kartika; Arifada, Tsania; Mahfudhoh, Maulia; Halisyibah, Utiyal Khukmafi (Amala Jurnal Pengabdian Kepada Masyarakat, 2025)
The ability to write scientific papers is essential for students, especially those in pesantren. However, challenges such as a lack of understanding of academic standards, finding credible references, and managing citations are still major obstacles. Therefore, Pondok Pesantren Griya Santri Mahabbah conducted training on using Mendeley and Publish or Perish applications to improve the quality of students' scientific work. This activity aims to strengthen technical competence in scientific writing while instilling a culture of literacy based on pesantren values. The training was held on 11 November 2024, with a ‘Participant Active Learning’ approach that involved the active participation of participants. The training stages included application installation, function introduction, and hands-on practice of using both applications. Mendeley is used for reference and citation management, while Publish or Perish helps search scientific literature efficiently. The results of the activity showed a significant increase in participants' understanding of the use of both applications. Students were better able to search for credible references and manage citations systematically, supporting faster and more structured completion of scientific papers. In addition, this training increases the opportunity for students to publish their work in national and international online journals. With the high enthusiasm of the participants, this activity is expected to encourage the development of scientific writing skills sustainably and support Santri to become a superior intellectual at the global level.